Hollow fibers made from a poly(3-hydroxybutyrate)/poly-ε-caprolactone blend (eXPRESS Polymer Letters)
Since poly(3-hydroxybutyrate) (PHB) is inherently brittle and possesses poor elastic properties, hollow fibers produced by melt spinning from pure PHB, as described in our earlier study [Macromolecular Materials and Engineering, 2010, 295/6, 585–594], do not meet the required needs regarding the mechanical performance. Besides hardly available PHB copolymers, also blend systems are known to enhance material properties and have thus been considered to be eligible to fabricate flexible or rather pliable hollow fibers based on PHB. Blends of PHB and poly-!-caprolactone (PCL) are promising for the application in tissue engineering due to the inherent biocompatibility and biodegradability. A wide range of PHB/PCL compositions have been prepared by melt extrusion. Thermal and mechanical properties of the obtained specimens were analyzed in order to identify miscibility and degree of dispersion as well as to determine the influence on the overall mechanical performance. Even though these constituents are known to be immiscible, PHB/PCL 70/30 was proven to be an adequate composition. This blend showed a highly increased elongation and was found to be easily processable by melt spinning compared to pure PHB. From this blend well defined dimensionally stable bendable hollow fibers were fabricated.